Lymphatic metastasis of signet ring cell gastric carcinoma located on mucosa layer - Nidal iflazoglu; Kivilcim Eren Erdogan; Ali Duran; Ozgul Duzgun; Figen Doran; Cem Kaan Parsak (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2016)
Early gastric cancer is described as tumors limited to mucosa and submucosa layers regardless of lymphatic metastasis. If early gastric cancer is limited to mucosa layer, metastasis of lymph node would be seen rarely. Further if intramucosal gastric tumors have signet ring cell histology and a size smaller than 2 cm, then lymph node metastasis are even rarer. In this paper we present a case that have signet ring cell gastric cancer limited to mucosa layer and had lymph node metastasis. It is decisive to evaluate depth of invasion and lymph node metastasis with preoperative tools to choose surgical treatment protocol. [Cukurova Med J 2016; 41(3.000): 577-580]